Differences in the statistics of competition in individual tennis according to the playing surface in male junior players of high-level. - Torres-Luque, G.; Fernández-García, AI.; Sánchez-Pay, A.; Ramírez, A.; Nikolaidis, PT. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
The aim of this study was to determine the performance indicators in two types of surface in male junior high-level players. 62 tennis single matches two different surfaces were analyzed (Australian Open versus Wimbledon). Data were collected from the official websites of the tournaments. Variables related to the match (3) service-related variables (10) and game-related variables (6) were analyzed. The results show a longer (p<0,05) duration of the match, point of second serve and percentage of points with second serve on grass than hard surface. It is the contrary in unforced errors and winners (p<0,05). Performance indicators according to the surface predicted to be unforced errors and winners that make the difference in junior male (SC =-.429;SC =-.376). It is concluded that is necessary to pay attention to these variables in junior players of high-level according to the playing surface.